Black Esophagus: Diagnostic Associations and Management Strategies - Gurvits, Grigoriy E. (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Gurvits GE. Black esophagus: Diagnostic associations and management strategies. Turk J Gastroenterol. 2022;33(5):451-452.